The effect of minimum wages on labour market flows: Evidence from Germany - Ronald Bachmann; Marion Penninger; Sandra Schaffner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Using a linked employer-employee data set on the German construction industry, we analyse the effects of the introduction of minimum wages in this sector on labour market dynamics at the establishment level, i.e. turnover and churning flows, as well as accessions and separations and their underlying worker flows. The fact that minimum wages in Germany are sector-specific enables us to apply a between approach using other industries as control groups in a difference-in-differences framework. Furthermore, we use a within approach with high-wage workers as control group. While the within approach shows that the minimum wage reduced worker flows in East Germany, the between approach yields positive effect on labour market dynamics in West Germany. Our results can be explained by differences between East and West Germany with respect to the bite of the minimum wage, as well as the much higher prevalence of posted workers in West Germany. Furthermore, spillover effects to highwage workers are likely to have played a role in East Germany. – – In dem Papier werden die Auswirkungen der Mindestlohneinführung im deutschen Bauhauptgewerbe auf Arbeitsmarktdynamiken untersucht, wobei die Analyse von Einstellungen und Trennungen sowie der damit zusammenhängenden Arbeitsmarktübergänge auf Betriebsebene erfolgt. Dabei kommt ein einzigartiger Linked Employer-Employee Datensatz zum Einsatz. Da der Mindestlohn zunächst nur im Bauhauptgewerbe eingeführt wurde, können Betriebe einer anderen Branche als Kontrollgruppe in einem Differenz-von-Differenzen-Ansatz genutzt werden (between-Ansatz). Zusätzlich wird ein within-Ansatz verwendet, bei dem Arbeitnehmer mit relativ hohem Lohn innerhalb des Bauhauptgewerbes als Kontrollgruppe dienen. Während der within-Ansatz zeigt, dass der Mindestlohn Arbeiterflüsse in Ostdeutschland reduzierte, bringt der between-Ansatz positive Effekte auf Arbeitsmarktdynamiken in Westdeutschland zutage. Diese Ergebnisse können auf Ost-West-Unterschiede hinsichtlich der Eingriffsintensität des Mindestlohns sowie die deutlich höhere Anzahl entsendeter Arbeitnehmer in Westdeutschland zurückgeführt werden. Zudem sind spillover-Effekte auf Arbeitnehmer mit relativ hohen Löhnen in Ostdeutschland wahrscheinlich.
Keywords: J23; J38; J42; J63; 330; minimum wage; labour market flows; difference-in-difference; linked employer-employee